MODEL PELAKSANAAN TATA KELOLA KEUANGAN DALAM PERSPEKTIF PEMERINTAHAN YANG BAIK (STUDI KASUS PADA SEKRETARIAT DPRD KABUPATEN PINRANG) - Darmawan, Darmawan (Economos : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine the financial governance model of the DPRD Secretariat of Pinrang Regency based on the perspective of good governance. It is hoped that the results of this study can be a source of reference for further researchers as well as information for the Secretariat of the DPRD of Pinrang Regency. Data collection techniques used are documentation, observation, and interviews with personal paper data sources and places. The analysis technique used is descriptive qualitative analysis. The results of the study indicate that financial governance at the DPRD Secretariat of Pinrang Regency has implemented the principles of good governance. Financial governance indicators used are community participation in regional financial management, transparency in regional financial management, accountability, and value for money.